Comparison of blistering of W bulk and film deposited by magnetron sputtering under helium irradiation. (August 2017) - Yu, Jiangang; Han, Wenjia; Chen, Zhe; Zhu, Kaigui
Highlights: W film deposited by magnetron sputtering is characterized by nanocrystalline structure. The difference behavior of He irradiation between W bulk and W film. Grain boundaries play an important role on the blistering after He irradiation. Abstract: In this work, the W bulk prepared by powder sintering and W film deposited by magnetron sputtering were simultaneously exposed to the helium ions with the energy of 60 keV and fluence of 1.0 × 10 22 m −2 at room temperature. The surface modifications induced by the helium irradiation were studied by scanning electron microscopy. After helium ion irradiation, numerous blisters were observed on the surface of both samples, some of which burst in various degrees. The formation of blisters is attributed to the high gas pressure in the helium bubbles. In addition, the different structures between W bulk and W film lead to the differences in density and size of blisters.